PERANCANGAN DESAIN ILUSTRASI SEBAGAI MEDIA BRANDING PENTOL KUAH BU SASTRI DI TAWANGMANGU - Haryanti, Kezia; Dewi, Yulia Krista; Cendana, Melkisedek (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
In this study, we met a meatball soup seller, Mrs. Sastri, who is located in Tawangmangu, precisely in front of Balekambang. Mrs. Sastri has been running her business since 2014. The results of the interview, Mrs. Sastri's meatball soup merchandise has never had an identity at all. And in this study will focus on designing illustration designs as a branding medium for Mrs. Sastri's meatball soup merchandise. This illustration design will later use elements related to meatball soup and use a logo as the identity of Mrs. Sastri's meatball soup merchandise. The method used in designing this illustration and logo design is a qualitative method. With the creation of illustration designs and logos on Mrs. Sastri's trading cart, it is hoped that it can help improve the branding of Mrs. Sastri's meatball soup.